Myricetin Inhibits SARS-CoV-2 Viral Replication by Targeting Mpro and Ameliorates Pulmonary Inflammation - Xiao, Ting; Cui, Mengqi; Zheng, Caijuan; Wang, Ming; Sun, Ronghao; Gao, Dandi; Bao, Jiali; Ren, Shanfa; Yang, Bo; Lin, Jianping; Li, Xiaoping; Li, Dongmei; et al. (Frontiers in Pharmacology, 2021)
The coronavirus disease 2019 (COVID-19) has spread widely around the world and has seriously affected the human health of tens of millions of people. In view of lacking anti-virus drugs target to SARS-CoV-2, there is an urgent need to develop effective new drugs. In this study, we reported our discovery of SARS-CoV-2 Mpro inhibitors. We selected 15 natural compounds, including 7 flavonoids, 3 coumarins, 2 terpenoids, one henolic, one aldehyde and one steroid compound for molecular docking and enzymatic screening. Myricetin were identified to have potent inhibit activity with IC50 3.684 ± 0.076 μM in the enzyme assay. The binding pose of Myricetin with SARS-CoV-2 Mpro was identified using molecular docking method. In the binding pocket of SARS-CoV-2 Mpro, the chromone ring of Myricetin interacts with His41 through π-π stacking, and the 3’-, 4’- and 7-hydroxyl of Myricetin interact with Phe140, Glu166and Asp187 through hydrogen bonds. Significantly, our results showed that Myricetin has potent effect on bleomycin-induced pulmonary inflammation by inhibiting the infiltration of inflammatory cells and the secretion of inflammatory cytokines IL-6, IL-1α, TNF-α and IFN-γ. Overall, Myricetin may be a potential drug for anti-virus and symptomatic treatment of COVID-19.